2015
DOI: 10.1002/hbm.22938
|View full text |Cite
|
Sign up to set email alerts
|

Regional specificity of aberrant thalamocortical connectivity in autism

Abstract: Preliminary evidence suggests aberrant (mostly reduced) thalamocortical (TC) connectivity in autism spectrum disorder (ASD), but despite the crucial role of thalamus in sensorimotor functions and its extensive connectivity with cerebral cortex, relevant evidence remains limited. We performed a comprehensive investigation of region-specific TC connectivity in ASD. Resting-state functional MRI and diffusion tensor imaging (DTI) data were acquired for 60 children and adolescents with ASD (ages 7–17 years) and 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
76
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 72 publications
25
76
2
Order By: Relevance
“…More specifically, convergent evidence from both datasets showed that reduced static iFC in ASD (''underconnectivity'') was related to increased temporal variability. Selecting an ROI pair (PCC-mPFC), for which underconnectivity findings have converged in the literature (Abbott et al, 2015;Assaf et al, 2010;Doyle-Thomas et al, 2015;Monk et al, 2009;von dem Hagen et al, 2012;Washington et al, 2013), mediation analysis showed that reduced static iFC was significantly impacted by increased temporal variability. The research questions motivating the current study were thus mostly affirmed by our findings: (1) iFC variability across time was atypically increased in ASD for several ROI pairings, that is, for PCC-mPFC, L LP-mPFC, and L Thal-R Thal pairs in Study 1 and for PCC-mPFC pair in Study 2; and (2) group differences in static iFC were significantly impacted by differences in the variability of iFC across time.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…More specifically, convergent evidence from both datasets showed that reduced static iFC in ASD (''underconnectivity'') was related to increased temporal variability. Selecting an ROI pair (PCC-mPFC), for which underconnectivity findings have converged in the literature (Abbott et al, 2015;Assaf et al, 2010;Doyle-Thomas et al, 2015;Monk et al, 2009;von dem Hagen et al, 2012;Washington et al, 2013), mediation analysis showed that reduced static iFC was significantly impacted by increased temporal variability. The research questions motivating the current study were thus mostly affirmed by our findings: (1) iFC variability across time was atypically increased in ASD for several ROI pairings, that is, for PCC-mPFC, L LP-mPFC, and L Thal-R Thal pairs in Study 1 and for PCC-mPFC pair in Study 2; and (2) group differences in static iFC were significantly impacted by differences in the variability of iFC across time.…”
Section: Discussionmentioning
confidence: 92%
“…Coordinates from previous studies were used to identify the seeds for the following regions: posterior cingulate cortex (PCC), medial prefrontal cortex (mPFC), left (L)/right (R) hippocampal formation (Hipp), L/R lateral parietal cortex (LP) (Van Dijk et al, 2010), pregenual anterior cingulate cortex (Prg ACC) (Di Martino et al, 2009), dorsal anterior cingulate cortex (Abbott et al, 2015), and L/R anterior insula (Ins) (Ebisch et al, 2011). All ROI masks, except for the Prg ACC, were defined as 10 mm radius spheres centered on the seed coordinates.…”
Section: Regions Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…These include structural MRI [11][12][13], intrinsic functional connectivity MRI (fcMRI) [14][15][16], diffusion tensor imaging (DTI) [17,18] and electroencephalography (EEG) [19,20]. Reported ASD abnormalities have been identified in the cerebellum [21] and cerebellar vermis [22], anterior cingulate gyrus [23], amygdala [24][25][26], hippocampus [24,27,28], and areas of the frontal [29][30][31], temporal [29,32] parietal lobes [30], caudate and putamen [29,33]. Additional imaging abnormalities in autism include impaired brain growth [24], cortical thickness [12,34], alterations in white matter architecture [18,35], and aberrant connectivity within the somatosensory, visual and default mode network [36].…”
Section: Introductionmentioning
confidence: 99%